Hydroponic cultivation training and its product processing for sustainable ecosystems in Lebakgede Area, Bandung City - Muhammad Achirul Nanda; Sophia Dwiratna; Kharistya Amaru (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Hydroponic cultivation is considered effective and efficient in terms of time, place, and cost. Postharvest handling must also be carried out properly, such as processing vegetables and fruit in hydroponic cultivation. Therefore, hydroponic plant cultivation training activities and the processing of their products play an essential role in urban communities, especially Lebakgede Area, Bandung City. In general, this service consisted of four main stages, including preparation and planning, implementation, evaluation, and follow-up. The investigation revealed that the majority of participants were housewives (43%), followed by community institutions (29%), others (14%), and entrepreneurs and civil servants (7%). In addition, 76% of participants were extremely satisfied, understanding, and interested in practicing hydroponic cultivation and processing its products. Based on the follow-up analysis, the participants have prepared a hydroponic house that will be managed together to support the supply of food ingredients in the Lebakgede Area Bandung City. This successful community service positively impacts the community by supplying high-quality vegetables. Therefore, this service activity can result in the formation of a sustainable hydroponic ecosystem and an increase in hydroponic expertise for future generations in Lebakgede Area, Bandung City.